Improving understanding of EEG measurements using transparent machine learning models - Roadknight, Chris; Zong, Guanyu; Rattadilok, Prapa (Springer Nature, 2019)
Physiological datasets such as Electroencephalography (EEG) data offer an insight into some of the less well understood aspects of human physiology. This paper investigates simple methods to develop models of high level behavior from low level electrode readings. These methods include using neuron activity based pruning and large time slices of the data. Both approaches lead to solutions whose performance and transparency are superior to existing methods.